ANALISIS KEMANDIRIAN BELAJAR SISWA SMP DALAM PEMBELAJARAN IPA DI MASA PANDEMI COVID-19 - Noor Rofiiqoh; Ahmad Qosyim (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2023)
This study aimed to analyze the students’ learning independence in science learning during the Covid-19 pandemic. This study used a quantitative descriptive. The data analysis technique used was descriptive statistics with data collection techniques using questionnaire sheets, interview sheets, and tests. This study involved 30 students of VIII-F class of State Junior High School 5 Gresik and the interview respondents were one science teacher. The results showed had high learning independence with seven indicators of learning independence in the high category and evaluating the process of learning indicator in the very high category. Therefore, it can be concluded that the high level of students’ learning independence had an effect on science learning outcomes.